2020
DOI: 10.1101/2020.05.04.074443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMARCB1 loss interacts with neuronal differentiation state to block maturation and impact cell stability

Abstract: Atypical teratoid rhabdoid tumors (ATRT) are challenging pediatric brain cancers which are predominantly associated with inactivation of the gene SMARCB1, a conserved subunit of the chromatin remodeling BAF complex, which has known contributions to developmental processes.To identify potential interactions between SMARCB1 loss and the process of neural development, we introduced an inducible SMARCB1 loss of function system into human induced pluripotent stem cells (iPSCs) which were subjected to either directe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In fact, data from our group demonstrate that Smarcb1 loss in mice results in severe brain developmental defects when occurring at an early timepoint during embryonic development [76]. In addition, the importance of SMARCB1 for neural development has been shown in human iPSCs [77]. Importantly, Smarcb1 alterations are linked to neurodevelopmental disorders and tumours of the developing brain such as atypical teratoid rhabdoid tumours (AT/RT).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, data from our group demonstrate that Smarcb1 loss in mice results in severe brain developmental defects when occurring at an early timepoint during embryonic development [76]. In addition, the importance of SMARCB1 for neural development has been shown in human iPSCs [77]. Importantly, Smarcb1 alterations are linked to neurodevelopmental disorders and tumours of the developing brain such as atypical teratoid rhabdoid tumours (AT/RT).…”
Section: Discussionmentioning
confidence: 98%
“…This is in line with our results showing major reorganizations related at a later stage of neural differentiation. Indeed, multiple NDD cell models have shown that the dysfunction of the chromatin organization leads to changed neuronal maturation (Calzari et al, 2020; Parisian et al, 2020; Su et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Genetically engineered human induced pluripotent stem cells (iPSC) have proven to be an effective, highly customizable system to model gliomagenesis in a species-specific manner, allowing for longitudinal analysis of human tumor biology from potential cell(s) of origin (Koga et al 2020;Miki et al 2022;Parisian et al 2020). Here, we employ an iPSC-based system to show that TP53 loss-and PDGFRA gain-of-function mutations, respectively, cooperate with heterozygous, chromosomal H3.3K27M to potentiate DMG tumor growth and alter cellular metabolism and intracellular signaling.…”
Section: Introductionmentioning
confidence: 99%